Spatial Patterns and Dynamics of some Halophytic Plants in the Hortobágy Region (Eastern Hungary) - Novák, Tibor (Ecological Questions, 2011)
Frequencies of 44 halophytic plants within 10 study sites in the Hortobágy were established, and the species were sorted by degree of salt tolerance. Number and frequency of β-mezohalin, α-mezohalin and oligohalin species was found higher than species number and frequencies of eu-, polihalin and hipersalin species. This shows, that the extremely salt-stress as environmental factor is rare on the Hortobágy.